Effects of design parameters on surface roughness of additively manufactured thin-walled structures (Journal of Additive Manufacturing Technologies, 2023)
Additive manufacturing (AM) has enabled the production of complex geometries that are not possible to be manufactured through traditional subtractive methods. Among the AM technologies, laser powder bed fusion (LPBF) has gained considerable attention in many engineering industries due to its capability to fabricate components with high resolution. The benefits of LPBF technology have also been utilized in the production of thin-wall structures in the aviation industry. Many internal thin-wall surfaces are retained as-build due to inapplicability of surface enhancement methods. Therefore, surface roughness of additively manufactured thin-wall structures is thoroughly sensitive to quality of AM process. This may adversely affect the mechanical properties of the end-product. Therefore, in this study, thin-wall specimens made of CoCr are fabricated through LPBF and effects of wall thickness, build angle, and angle of the laser incidence on the surface roughness are investigated. For that purpose, printed surface topologies are analyzed using a focus variation device and relationship between the control parameters and standard surface roughness metrics is presented.
Keywords: Surface Roughness; Thin Wall; LPBF; Design for AM; Build Angle; Laser Incidence Angle